Parasite community of the pelagic thresher Alopias pelagicus (Lamniformes) as additional indicator of trophic network status and functioning - Santoro, Mario; Occhibove, Flavia; Cusano, Luigi Maria; Palomba, Marialetizia; Pacheco-Chaves, Bernald; Carvajal-Rodríguez, José Miguel; Monge-Amador, Monica; Rojas, Alicia; Solano-Barquero, Alberto (Scientific reports, 2025)
The majority of marine parasites are trophically transmitted, exhibiting a complex life cycle, thus, parasite communities investigation is a valuable source of information on trophic network status. Parasite communities of sharks, which have high structural importance within trophic webs, might well be included among bioindicators of trophic network functioning. Here, we present the first study on parasite communities of the pelagic thresher Alopias pelagicus , in the eastern Pacific, a highly biodiverse area, subject to the threat of overfishing. Results indicated that the parasite community exhibited greater richness, abundance, and diversity compared to those reported in other shark species and locations, suggesting that the trophic network in the area may still be resilient to anthropogenic pressures. Differences found among sex, individuals of different size, and across sampling sites with different maximum depths confirmed that both biotic and abiotic factors influence parasite communities, which are known to be sensitive to such variables. Our findings supported the use of parasite communities in high trophic level predators as reliable and effective indicators of the trophic network status, advocating for their inclusion as an additional tool in biodiversity conservation.